Tasya Farasya’s Credibility as Influencer and “Tasya Farasya Approved” Logo as Endorsement Effect Impact Followers’ Purchase Intention - Suwandy, Tasya Julia; Heksarini, Ariesta (INDO PUBLISHING, 2026)
This study aims to analyze the influence of influencer credibility and endorsement of the